The coexistence of hypercalcemia, osteoporosis and thymic enlargement in graves’ disease: a case report - Yan, Dandan (BMC Endocr Disord, 2020)
BACKGROUND: Hyperthyroidism-induced hypercalcemia has been reported previously, but hypercalcemia accompanied by severe osteoporosis and significant thymic enlargement in patients with hyperthyroidism is quite rare. We report the coexistence of hypercalcemia, osteoporosis and thymic enlargement in a patient with Graves’ disease. CASE PRESENTATION: A 22-year-old female was diagnosed as Graves’ disease with obviously elevated serum calcium and reduced parathyroid hormone levels. Dual-energy x-ray absorptiometry and chest enhanced computer tomography (CT) revealed severe osteoporosis and a significant enlargement of thymus. After the successful control of hyperthyroidism with methimazole, hypercalcemia was corrected, bone mineral density was improved and thymus also shrank obviously. CONCLUSION: This is a very rare case of hypercalcemia accompanied by severe osteoporosis and significant thymic enlargement induced by Graves’ disease. In clinical practice, examination of thymus and bone density should be considered when a patient with Graves’ disease was present with hypercalcemia.